Inter-examiner and intra-examiner reliability of optical coherence tomography angiography in vascular density measurement of retinal and choriocapillaris plexuses in healthy children aged 6–15 years - Diao, Kai; Huang, Xiaomin; Yao, Mingyu; Li, Jiawei; Fan, Feifei; Pan, Hongxian; Yu, Jinjin; Yang, Yizhou; Lu, Weiwei; Lian, Hengli; Wang, Qinmei; Huang, Jinhai; et al. (Frontiers in Medicine, 2023)
Objective: This study aimed to test the inter-examiner and intra-examiner reliability of macular vascular density (VD) measurement of retinal and choriocapillaris plexuses in healthy children using optical coherence tomography angiography (OCTA). Materials and Methods: Ninety-two school children were prospectively recruited. Macular OCTA images (6 × 6 mm) were obtained thrice by two examiners using the RTVue-XR Avanti OCT system. The coefficient of variation (COV), intraclass correlation coefficient (ICC), and the Bland–Altman plots were used to evaluate the repeatability and reproducibility. Results: Ninety participants aged 6–15 years were enrolled; two participants were excluded because of poor image quality. In the retina, the reproducibility and repeatability of VD became poorer from superficial to deep retinal capillary plexus (superficial: COV = 4.61%–11.11%; intermediate: COV = 7.73%–14.15%; deep: COV = 14.60%–32.28%). For both reproducibility and repeatability, the ICC ranged from moderate to high (superficial plexus: ICC = 0.570–0.976; intermediate plexus: ICC = 0.720–0.968; deep plexus: ICC = 0.628–0.954). In the choroid, the inter-examiner reproducibility and intra-examiner repeatability of VD measurement of choriocapillaris were excellent in the macula, fovea, parafovea, and perifovea (COV = 1.00%–6.10%; ICC = 0.856–0.950). The parameters of the foveal avascular zone (FAZ) also showed significant reproducibility and repeatability (COV = 0.01%–0.21%; ICC = 0.743–0.994). Conclusions: The VD measurements of choriocapillaris and FAZ parameters using OCTA showed excellent inter-examiner and intra-examiner reliability in school children. The reproducibility and repeatability of VD of three retinal capillary plexuses depended on the depth of the retinal capillary plexus.